Pengaruh Brand Image Media Sosial Terhadap Keputusan Pembelian - Fitriani, Diana (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2024)
Research entitled the influence of social media brand equity on purchasing decisions was carried out to provide an overview of the social media that consumers choose to help them make purchasing decisions. uses a form of causality which states that the research is related to cause and effect research. The main variable or independent variable in the research is related to brand strength (X1), brand uniqueness (X2), and brand favorability (X3) while the dependent variable is the purchasing decision (Y) on the social media chosen to carry out product purchase transactions. Testing was carried out using multiple linear regression, namely validity and reliability tests and continued using the classical assumption test or ordinary least squares (OLS) test which consists of normality test, multicollinearity test, autocorrelation test, heteroscedasticity test and linearity test. The multiple linear regression test is related to the situation in providing an overview regarding the test of the influence between the independent variable and the dependent variable. Based on the number of respondents obtained using the accidental sampling technique, 98 people stated that social media which had been determined based on the highest rating for use in Indonesia in sequence, namely WhatsApp, Instagram, Facebook and TikTok, had features that represented needs in the consumer process of making purchasing decisions starting from the favorable brand variable (X3) is 78.30%, then the strong brand (X1) is 55.70%, and uniqueness (X2) is 38.7% for purchasing decisions (Y) is 81.50%. So that social media brand equity, which consists of three categories, is stated to have a significant influence on consumer purchasing decisions, respectively.